Experimental Investigation of Wave-Induced Hydroelastic Vibrations of Trimaran in Oblique Irregular Waves - Haoyun Tang; Huilong Ren; Hui Li; Qi Zhong (Shock and Vibration)
The irregular wave condition, especially the oblique irregular wave condition, is the actual circumstances when trimaran is sailing in sea. In order to identify the characteristic of the wave-induced hydroelastic vibration in irregular waves, as well as investigate the change of vibration in different oblique irregular wave conditions, trimaran model tests were conducted to measure vibrations, wave impact, and motion under different azimuth and wave height. The vibration on main hull, side hull, and cross-desk is measured and analyzed separately to observe the influence of irregular wave in different structural parts. The longitudinal vibration, transverse vibration, and torsion are also included in the model tests measurement to investigate the relationship between these vibration deformation components and parameters of the irregular waves. The wave-induced hydroelastic vibrations and whipping effect is extracted and analyzed to find influence of whipping and springing on the total vibration. Based on the analysis, the dangerous positions and the critical waves condition is introduced to ensure that the subsequent structural strength assessment is more reliable.